Morphological and Molecular Characterization of Phytophthora colocasiae Obtained from Fine Spatial Scale - George, Akshara; Jeeva, ML; Nath, Vishnu S; Sreelatha, GL; Sujina, MG; Makeshkumar, T (JOURNAL OF ROOT CROPS, 2017)
Taro leaf blight caused by the oomycete pathogen Phytophthora colocasiae is the most devastating disease of taro with yield loss of 30-50%. The methods commonly used for P. colocasiae identification and isolation often include direct isolation from infected leaf tissue on semi-selective media or baiting from soil with leaf discs followed by isolation. Several studies have revealed the effect of culture media and physiological parameters on mycelial growth and sporangium production of Phytophthora sp. In view of this, the main objective of this research was to evaluate growth characteristics and sporulation of P. colocasiae obtained from fine spatial scale in different culture media. Morphological and molecular characterization was employed for assessing the genetic variability of those P. colocasiae isolates. All the isolates exhibited similar growth pattern and colony morphology within the individual media tested. Whereas, ITS characterization revealed detectable polymorphism among the P. colocasiae isolates. Maximum growth rate was recorded on onion agar followed by tomato agar, whereas soybean agar showed less linear growth after 7 days of inoculation. Evaluation of sporulation events revealed that carrot agar can induce sporulation earlier than other culture media tested. Physiological factors such as temperature, pH and incubation period greatly influenced the mycelial growth of the pathogen. Results of this study suggest that optimal isolation rates of P. colocasiae from infected leaf tissues are achieved by culturing fresh leaf tissues on Ampicillin supplemented PDA medium (100 mg l-1).